Negosiasi Pendidikan Islam dan Teknologi Terhadap Perubahan Global “Sebuah Responisasi Terhadap Era Revolusi Industri 4.0” - Zulkifli, Zulkifli; Khatami, M.; Muhammadiyah; Zulkarnainsyah (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2023)
Islamic education, which has gone through a long enough period, is now in contact with such a large wave of technology. So that the issue of the dichotomy of knowledge and the Islamization of science no longer seems to be the dominant issue in Islamic education. The wave of technology that has touched all aspects of people's lives, especially in Indonesia which is the market for this progress. This was responded quite well by Islamic education. Not only that, religion also contributes to giving a good response to global changes. Keywords: Islamic Education, Technology, Religion